Emma's turtle - Bunting, Eve, 1928-2023.; Winborn, Marsha (Honesdale, Pa. : Boyds Mills Press, 2007)
When Emma's box turtle digs his way out of his pen, he imagines that he is having adventures in Africa, India, and other faraway lands that Emma has described to him.
A Junior Library Guild selection
Accelerated Reader/Renaissance Learning
Keywords: Box turtle -- Juvenile fiction; Turtles -- Juvenile fiction; Adventure and adventurers -- Juvenile fiction; Picture books for children; Children's stories -- Pictorial works